Mitos Weton pada Pernikahan Masyarakat Desa Gedangan Lamongan: Kajian Mircea Eliade - Apria Ningrum, Velida; Nabila Fajriyanti Muhyin; Agoes Moh Moefad (IAIN Madura, 2023)
The myth remains a frequently encountered phenomenon in society, particularly among the Javanese people known for their spiritual sharpness. This article explains the myth of calculating